Pemenuhan Hak Anak Berkebutuhan Khusus (ABK) Perspektif HAM & Pendidikan Islam di MINU Purwosari Metro Utara - Aisyah, Nurul; Amalia, Dian Risky (CV. Creative Tugu Pena, 2020)
Gaining education for Children with Special Needs was essential to engage their knowledge and skill. This article aimed to find out how to fulfill the right Children with Special Needs on human rights and Islamic education perspective at “Madrasah Ibtidayah Nahdlatul Ulama (MINU). Qualitative method was applied in this research. The participants of this research were students in the grades two and five VI at Madrasah Ibtidayah Nahdlatul Ulama (MINU) at Purwosari Metro Utara) . Collecting data used observation, interview, and documentation. The result show that children with special needs has been effort to obtain treatment in accordance with their talents, interests, abilities, and disorders, obtain religious education in accordance with their religion, follow the relevant education program on the basis of continuing education, and obtain assistance in learning facilities and scholarships. Keywords: Children with Special Needs, Human Right Perspective, Islamic Education Perspective.